LEXICAL AND SEMANTIC MEANS OF REPRODUCING THE SPANISH DIALOGUE IN THE UKRAINIAN TRANSLATION OF THE NOVEL А. PEREZ-REVERTE’S ‘QUEEN OF THE SOUTH’ - Shelemekha, Yuliia; Andriievska, Ella (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
The article is devoted to the study of the problems of translation of dialogue speech in the novel ‘The Queen of the South’ by the Spanish writer A. Perez-Reverte. The analysis of the material made it possible to identify the main types of dialogues in a work of fiction and to determine the leading strategies and techniques of their interpretation in the Ukrainian language. The features of reproduction of dialect, slang and jargon vocabulary in the characters’ remarks are considered; the level of achieving adequacy of the Ukrainian translation is determined. _____________ References: • Het’man, Z. O. (2004). Zaholnonatsional’na ispans’ka mova ta ispans’ke rozmovne movlennia v konteksti ibero-romans’koi vzaemodii [National Spanish Language and Spanish Colloquial Speech in the Context of Ibero-Romance Interaction]. Naukovi zapysky Instytutu filolohii Kyivs’koho universytetu. Retrieved from https://language-science.com • Zorivchak, R. P. (2007). Ukraińs’kyi khudozhnii pereklad yak natsietvorchyi chynnyk [Ukrainian Literary Translation as a Nation-Building Factor]. Zarubizhna literatura, 1–5. Retrieved from https://ekhnuir.karazin.ua/server/api/core/bitstreams/91df5170-9bb5-43c6-8425-6d7ed45441af/content • Kolomiiets’, L. (2017). Aktual’ni pytannia khudozhnoho perekladu na yevropeiskykh naukovykh maidanchykakh [Current Issues of Literary Translation on European Academic Platforms]. Ukrains’ka literaturna hazeta, 19(22), 19. Retrieved from https://modernpedagogy.com • Koptilov, V. V. (2002). Teoriia i praktyka perekladu (2-e vyd.) [Theory and Practice of Translation (2nd ed.)]. Kyiv: Yunyvers. • Korunets’, I. V. (2008). Bilia vytokiv ukraiins’koho perekladoznavstva [At the Origins of Ukrainian Translation Studies]. Vsesvit: Zhurnal inozemnoi literatury, 188–194. Retrieved from https://modernpedagogy.com • Koshchii, Yu. P. (n.d.). Rozmovni elementy ukraiins’koho ta ital’ijs’koho perekladiv diolohiv ispans’koi trahedii F. H. Lorky "Kryvave vesillia" [Conversational Elements of Ukrainian and Italian Translations of Dialogue in the Spanish Tragedy by F. G. Lorca "Blood Wedding"]. Naukovyi visnyk Khersons’koho derzhavnoho universytetu. Seriia "Linhvistyka", 20, 248–254. Retrieved from https://www.sciencedirect.com • Cherednychenko, O. I. (2017). Pereklad. Kultura. Identychnist’ [Translation. Culture. Identity]. Kyiv: Vydavets’ Zaslavs’kyi O. Yu. • Bosque Muñoz Ignacio, Gutiérrez-Rexach Javier Fundamentos de sintaxis formal (2009).Ediciones Akal, S.A.; 1st edition. 800 р. • Diccionario de la Real Academia Española. URL: http://buscon.rae.es/ • Forgas Berdet, Esther (2007) “El lugar de la literatura, la historia y el arte en la enseñanza de español a extranjeros”, http://dialnet.unirioja.es/servlet/articulo?codigo=2341079 • Hurtado Albir, A. Traducción y traductología: Introducción a la traductología. Cátedra, 13a ed. 2022. 696 p. • Muñoz Martín R. Lingüística para traducir, Narceloma Teide, 1995. • Rabadán R. Equivalencia y traducción. Problemática de la equivalencia translémica inglés español, León, Universidad de león, 1991. • Verba H. El cambio semántico como fuente de los falsos amigos del traductor - Mundo Eslavo, – Granada: Ed. Universidad de Granada, 2019. Nº18. Pp. 188-201. • Yebra, Valentín García Teoría y práctica de la traducción, 2 t., Madrid, Gredos, 198/.2. • Pérez-Reverte Arturo La Reina del Sur. (2002). Santillana Ediciones Generales. 522 p. URL: https://readli.net/chitat-online/?b=173156&pg=1 • Peres-Reverte Arturo Koroleva Pivdnja. Roman / per. z ispan. I. Shevchenko. Harkiv: VD «Fabula», 2023. 432 s.